Pemberdayaan Ibu-Ibu Kebersihan Melalui Pelatihan Kewirausahaan Dipondok Modern Al-Rifa’ie - Abdus Salam; Silvi Nur Aini; Febriati Nadira; Amalia Nur Latifa; Arya Mahardika Prasetya (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2026)
The Community Service and Empowerment Lecture Program (KP2M) was implemented as a concrete form of providing real contributions to improving the economic welfare of the community, especially for the cleaning staff of the Al-Rifaie Modern Islamic Boarding School. This (KP2M) activity was implemented to provide practical skills-based entrepreneurship training, focusing on making simple food products such as chocolate rolled omelettes and mayo spring rolls. This training lasted for five days, using a participatory approach through lectures, interactive methods, direct demonstrations, and independent practice. The results of the Community Service and Empowerment Lecture Program (KP2M) showed that this training significantly improved the community through cooking skills, displayed community enthusiasm during the training, and showed a strong interest in starting a home business independently.This training also provides technical skills and has a positive psychological impact, increasing participants' confidence in building businesses. Challenges in this KP2M activity include limited equipment for direct demonstrations and a limited timeframe. Overall, the program has been effective in encouraging community economic empowerment, particularly for women of lower productive age. Therefore, it is recommended that supporting facilities be improved and the program extend for more optimal and sustainable results.